2019
DOI: 10.5590/ijamt.2019.18.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Self-Service Technologies Among Banking Customers: A Revisit

Abstract: The introduction of self-service technologies (SSTs) in the banking industry has been emerging as one of the significant business drivers that facilitate customers in operating their bank accounts. Considering this, the present study has made an attempt to pierce the existing literature with reference to the adoption of SSTs among banking customers. Particularly, the intent of the present article is to explore various personal (e.g., optimism, socioeconomic characteristics) and technology characteristics (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As an example, Podder (2005) did explore Internet Banking adoption modes through the integration of Technology Adoption Model with another model, perceived characteristics of innovation, created by Moore and Benbasat (1991), but an insight into these studies of this nature has raised certain issues. Magotra et al (2019) emphasized that the studies of this nature indicate that while formation of the framework for the study, researchers have taken a favoured model (based on their liking and perception or referral researches) also states that they have largely ignored the contributions of other alternative models in explaining SST's adoption behaviour of the consumers (Venkatesh et al, 2003). Further, it has been identified that certain constructs used by the researchers for exploring the QR Code payment modes and NFC adopted payment modes decision of the customers have been developed in contexts other than self-service technologies offered to the banking consumers.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Podder (2005) did explore Internet Banking adoption modes through the integration of Technology Adoption Model with another model, perceived characteristics of innovation, created by Moore and Benbasat (1991), but an insight into these studies of this nature has raised certain issues. Magotra et al (2019) emphasized that the studies of this nature indicate that while formation of the framework for the study, researchers have taken a favoured model (based on their liking and perception or referral researches) also states that they have largely ignored the contributions of other alternative models in explaining SST's adoption behaviour of the consumers (Venkatesh et al, 2003). Further, it has been identified that certain constructs used by the researchers for exploring the QR Code payment modes and NFC adopted payment modes decision of the customers have been developed in contexts other than self-service technologies offered to the banking consumers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Further, it has been identified that certain constructs used by the researchers for exploring the QR Code payment modes and NFC adopted payment modes decision of the customers have been developed in contexts other than self-service technologies offered to the banking consumers. As emphasised by Magotra et al (2019), perceived usefulness has been developed in Technology Adaption Model (Davis et al, 1989), with reference to employees/customers using information technology at their workplace. However, perceived usefulness has been developed in context other than SST's the construct has been widely used with reference, to the adoption of QR Code payment solutions and NFC enabled Payment solutions among the banking consumers (Murali & Mallikarjuna, 2014).…”
Section: Review Of Literaturementioning
confidence: 99%
“…According to technology self-efficacy and adoption of smart banking may be positively influenced by the perceived ease of use. Nonetheless, some researchers have found that there was no significant impact on attitude towards self-banking channels from the perceived ease of use (Aboelmaged & Gebba, 2013;Magotra et al, 2019). However, most of the researchers found that adoption of technology based selfservice banking services may increase with the ease of use (D.A.…”
Section: Literature Reviewmentioning
confidence: 99%